Complementary Contribution of Fungi and Bacteria to Lignocellulose Digestion in the Food Stored by a Neotropical Higher Termite - Moreira, Edimar A.; Persinoti, Gabriela F.; Menezes, Letícia R.; Paixão, Douglas A. A.; Alvarez, Thabata M.; Cairo, João P. L. Franco; Squina, Fabio M.; Costa-Leonardo, Ana Maria; Rodrigues, Andre; Sillam-Dussès, David; Arab, Alberto (Frontiers in Ecology and Evolution, 2021)
Lignocellulose digestion in termites is achieved through the functional synergy between gut symbionts and host enzymes. However, some species have evolved additional associations with nest microorganisms that collaborate in the decomposition of plant biomass. In a previous study, we determined that plant material packed with feces inside the nests of Cornitermes cumulans (Syntermitinae) harbors a distinct microbial assemblage. These food nodules also showed a high hemicellulolytic activity, possibly acting as an external place for complementary lignocellulose digestion. In this study, we used a combination of ITS sequence analysis, metagenomics and metatranscriptomics to investigate the presence and differential expression of genes coding for Carbohydrate-Active Enzymes (CAZy) in the food nodules and the gut of workers and soldiers. Our results confirm that food nodules express a distinct set of CAZy genes suggesting that stored plant material is initially decomposed by enzymes that target the lignin and complex polysaccharides from fungi and bacteria before the passage through the gut, where it is further targeted by a complementary set of cellulases, xylanases, and esterases produced by the gut microbiota and the termite host. We also showed that the expression of CAZy transcripts associated to endoglucanases and xylanases was higher in the gut of termites. An additional finding in this study was the presence of fungi in the termite gut that expressed CAZy genes. This study highlights the importance of externalization of digestion by nest microbes and provides new evidence of complementary digestion in the context of higher termite evolution.